Gemeentediakonaat – Nuut gedink - Breed, Gert (Verbum et ecclesia, 2023)
The diaconate of the congregation - Considered anew. From the earliest times, the content given to the diaconate of the congregation varied greatly from denomination to denomination. Different methods and sources were used to determine the content and essence of the diaconate. This article attempts to look at the diaconate of the congregation from a new angle to determine what the diaconal task of the congregation can be. Use is made of previous exegetical work done by the author (2018) of this article. He exegeted specific texts in the New Testament in depth with the research question of what meaning possibility of the diacon words (diakoneo, diakonos, diakonia) the authors had in mind when using the words in those texts. These results are used in an attempt to establish what the diaconate can mean when it is built on the meaning contents of the deacon-words. The result is that new insights are exploited and practically applied to the diaconate. The conclusion of this article is that the deacons should work towards involving each member in the diaconate by guiding them to discover their gifts and to encourage them to use those gifts. The members undertake to do specific service work and to be held accountable for it. In this way, the congregation distributes the grace of God and the diaconate takes on a missionary character and God can work mightily through the diakonia of each member. Intradisciplinary and/or interdisciplinary implications: An exegetical study of the New Testament informs the discussion and opens a dialogue between Practical Theology and Hermeneutics. The results of this research have implications for church polity. The outcome of the practical implementation of the results can be a field of study for pastoral counselling, psychology and sociology.